2022
DOI: 10.3389/fpsyg.2022.968472
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling festival participation and tourists’ revisit intention

Abstract: Storytelling is getting increasing attention as one of the effective strategies for revitalizing the local festivals and even regional economies. Yet, the mechanisms through how storytelling helps the success of local festivals are still relatively less known. Using the data from 322 individuals who participated in local festivals using storytelling, our results showed that local festival storytelling is positively related to tourists’ revisit intention. Furthermore, the positive relationship between local fes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This observation is consistent with that achieved by Gilliam and Zablah (2013), who stressed the effectiveness of product-centric narratives in driving consumer actions toward making purchases. Similarly, Ko et al (2022) provided empirical evidence supporting the dual mediation role of authenticity and positive emotions in enhancing the connection between storytelling on local festivals and the intention to revisit. In addition, Al Ashi (2022) found that immersion in the restaurant story presented on social media has the greatest impact on consumer purchase intention, leading to a positive attitude mediated by social media engagement.…”
Section: Discussionmentioning
confidence: 86%
“…This observation is consistent with that achieved by Gilliam and Zablah (2013), who stressed the effectiveness of product-centric narratives in driving consumer actions toward making purchases. Similarly, Ko et al (2022) provided empirical evidence supporting the dual mediation role of authenticity and positive emotions in enhancing the connection between storytelling on local festivals and the intention to revisit. In addition, Al Ashi (2022) found that immersion in the restaurant story presented on social media has the greatest impact on consumer purchase intention, leading to a positive attitude mediated by social media engagement.…”
Section: Discussionmentioning
confidence: 86%
“…It is a fact that in the past around three-year pandemic, the stagnation of festival tourism has actually brought losses in multiple aspects, involving regional economy, cultural transmission, and sustainable development of communities and society [1,14,15]. The viewpoint has been made that it is crucial to reexamine the attributes or performance, benefits, value of festival tourism, tourists' participation or willingness to consume a festival/event product as well as their experience quality even subjective wellness during a festival trip [1,[16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is a fact that there has been a marked change in customers' attitudes and risk perception of consuming tourism products/services, and the perceived image also plays a significant role in affecting their behavioral intentions after the pandemic [1,16,18,19]. Previous studies indicated that tourists tend to visit the low-risk tourism areas, and consume those tourism products and services that are more familiar to them [7,18,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%